Selling order in a sequential auction - Hikmet Gunay; Xin Meng; Victor Perez (Osaka University, Institute of Social and Economic Research (ISER), 2024)
In a second-price sequential auction with both global and local bidders, we explore the optimal order for selling heterogeneous goods to maximize efficiency or revenue. Our findings indicate that selling the good with very small variance (almost-zero variance) first yields higher revenue, while selling it second results in an efficient outcome with probability almost 1. We link the optimal selling order to the likelihood of various inefficient outcomes. Specifically, selling the good with small variance first increases the probability of ex-post loss for the global bidder, boosting the seller's revenue at the expense of overall social welfare.
Keywords: D44; D82; 330; Sequential Auctions; Multi-dimensional values; Simulations